Epidemiological characteristics of imported cases of malaria in the Zaporozhye region for 2001-2019 - El Kandoussi, Sara; Onishchenko, T. E.; Оніщенко, Тетяна Євгенівна (Запорізький державний медичний університет, 2021)
Topicality. Malaria is the most common endemic disease in the world, with a transmissible mechanism of infection, and is regularly registered in 91 countries. More than 220 million cases are registered annually. In the conditions of population unregulated migration problem of imported malaria in non-endemic regions and introduction multidrug-resistant strains of malaria pathogens in the territory, which were previously free from them, becomes very important.